Perspectives on cancer therapy—synthetic lethal precision medicine strategies, molecular mechanisms, therapeutic targets and current technical challenges - Shixuan Peng; Mengle Long; Qisheng Chen; Zhijian Yin; Chang Zeng; Wanyong Zhang; Qingyang Wen; Xinwen Zhang; Weiqi Ke; Yongjun Wu (Cell Death Discovery)
Abstract In recent years, synthetic lethality has become an important theme in the field of targeted cancer therapy. Synthetic lethality refers to simultaneous defects in two or more genes leading to cell death, whereas defects in any single gene do not lead to cell death. Taking advantage of the genetic vulnerability that exists within cancer cells, it theoretically has no negative impact on healthy cells and has fewer side effects than non-specific chemotherapy. Currently, targeted cancer therapies focus on inhibiting key pathways in cancer. However, it has been found that over-activation of oncogenic-related signaling pathways can also induce cancer cell death, which is a major breakthrough in the new field of targeted therapies. In this review, we summarize the conventional gene targets in synthetic lethality (PARP, ATR, ATM, WEE1, PRMT) and provide an in-depth analysis of their latest potential mechanisms. We explore the impact of over-activation of pathways such as PI3K/AKT, MAPK, and WNT on cancer cell survival, and present the technical challenges of current research. Important theoretical foundations and insights are provided for the application of synthetic lethal strategies in cancer therapy, as well as future research directions.